P142 Effectiveness and reliability of pre-discharge jaundice assessment tools: a quality improvement project. (June 2019) - Rehman, Liqa ur; Hussein, Mushtaq; Shori, Naeem; Ahmed, Riaz; Zia, Muhammad; Azam, Muhammad
Abstract : Background: Visual inspection using the Kramer index was the only tool available to detect the degree of jaundice at our hospital.A retrospective audit done at this hospital showed that only 13%of neonates required phototherapy and 87% were pricked unnecessarily, adding to parental anxiety. Therefore, we decided to launch a one-year prospective study (July 2016–2017). Aim: To determine the diagnostic accuracy of two pre-discharge jaundice assessment tools and to correlate these measurements with SBR results in neonates >35 weeks in order to implement a safe, cost-effective&patiently friendly alternative to improve quality of care. Method: All health care professionals were briefed on the guidelines set out in NICE 4 &AAP 1 for visual assessment of jaundice.In the first 6 months, any neonate being visually assessed as significantly jaundiced (below nipple line) was referred for SBR intake.Results were then plotted on nomograms for further action. 1, 3, 4 During the next six months, a TcB was purchased and all health care professionals were briefed on equipment usage and criteria for further action 1, 3, 4 . A pre-discharge TcB check was performed on all neonates. SBR was taken within an hour of TcB if it measured >200µmol/l in term & >170µmol/l in late pre-term neonates 1, 3, 4 .Further follow up was arranged as per risk designation on nomogram (Recommendation 3.0, 6.12, AAP). The correlation of the above variables was analysed.Reliability of TcB was then determined in both terms and pre-terms. Inclusion criteria: Age:<14 days, >38weeks&>24 hoursofage, between35–37+6weeks&>48 hoursofage 1, 3, 4 Exclusion criteria: <35weeksgestation, risk factors as listed in AAP(Figure 3) 1, 3, 4 . Results: Reliability of TcB:Sample size:72 Average difference: Term±22µmol/l, Pre-term ±29µmol/l Conclusion: Visual estimation of bilirubin levels for the degree of jaundice can lead to errors with 70% sensitivity and 89% specificity.TcB, however, is a non-invasive, cost effective and reliable alternative tool with 100% sensitivity and 96% specificity.TcB >200µmol/l in term and >170µmol/l in late pre-terms is less accurate with a mean difference of ±22µmol/l and ±29µmol/l respectively, if SBR is repeated within an hour of TcB. Recommendation: All infants should be monitored routinely for the development of jaundice & be evaluated for risk factors.Excluding high risk neonates, a pre-discharge TcB should be performed on all neonates & be interpreted+plotted on nomogram according to the infants'age in hours.Appropriate follow up & further testing may be indicated depending on the infant's risk designation on nomogram.(Recommendation 3.0, 6.12, AAP) 1